2012
DOI: 10.1053/j.gastro.2011.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Releases Lipid That Promotes Fibrogenesis by Activated Hepatic Stellate Cells in Mice and in Human Tissues

Abstract: BACKGROUND & AIMS The pathogenesis of liver fibrosis involves activation of hepatic stellate cells, which is associated with depletion of intracellular lipid droplets. When hepatocytes undergo autophagy, intracellular lipids are degraded in lysosomes. We investigated whether autophagy also promotes loss of lipids in hepatic stellate cells to provide energy for their activation and extended these findings to other fibrogenic cells. METHODS We analyzed hepatic stellate cells from C57BL/6 wild-type, Atg7F/F, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
569
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(604 citation statements)
references
References 31 publications
26
569
2
7
Order By: Relevance
“…Hernández‐Gea et al . found that inhibition of autophagic function in primary mouse HSCs and mice following reduced fibrogenesis and matrix accumulation, which suggested autophagy promoted HSCs activation 21. Similar to previous study 18, we found that naringin induced autophagic activity in HSCs.…”
Section: Discussionsupporting
confidence: 89%
“…Hernández‐Gea et al . found that inhibition of autophagic function in primary mouse HSCs and mice following reduced fibrogenesis and matrix accumulation, which suggested autophagy promoted HSCs activation 21. Similar to previous study 18, we found that naringin induced autophagic activity in HSCs.…”
Section: Discussionsupporting
confidence: 89%
“…LDs are characteristic of resident HSCs and their presence and induction suppress HSCs activation 33, 34. Autophagy contributes to the intracellular catabolism of lipids in HSCs 8. Our data revealed an increased number of LDs in LX‐2 cells treated with miR‐30a mimics (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Data relating autophagy to liver fibrogenesis first emerged independently by two different groups that showed evidence for an increase of autophagy in activated HSC [98,99], both suggesting that autophagy has a first role in the loss of perinuclear lipid droplets (containg retinyl esters) that accompanies trans-differentiation of quiescent HSC towards the activated phenotype. In a first study autophagy was detected during in vitro activation of primary mouse HSCs by investigating typical autophagyrelated markers, including LC3.…”
Section: Autophagy and Liver Fibrogenesismentioning
confidence: 99%